Peningkatan Kapasitas Produksi Olahan Gropak di Desa Karangdadap, Kecamatan Kalibagor, Kabupaten Banyumas - Zulkifli, Lutfi; Putri, Dindy Darmawati; Wijayanti, Irene Kartika Eka (Darmabakti : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2024)
The LPPM Research-Based Community Service Program at Jenderal Soedirman University was implemented by increasing the Gropak Processed Production Capacity in Karangdadap Village, Kalibagor District, Banyumas Regency. Along with the development of the Gropak SME industry, there are currently several obstacles that industry players must face, especially during the Covid 19 pandemic. Community service activities are carried out to help improve community welfare by covering several activities including production assistance, delivery of production tools and assistance as well as certification assistance halal